2019
DOI: 10.1002/adom.201801681
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Electrically Driven Ultraviolet Plasmonic Lasers

Abstract: Plasmonic lasers, which make use of the strong confinement of surface plasmon polaritons (SPPs), are key components to realize ultracompact coherent light sources at deep subwavelength scale. Currently, large metal and radiation losses of their metallic cavities limit electrically driven plasmonic lasers operation mainly at cryogenic temperature, where sufficient gain can be obtained. It is a crucial challenge to accomplish high performance electrically driven plasmonic lasers operated at room temperature. Ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…The generation of electron-hole recombination occurring in the GaN region is insignificant. However, the used MgO interlayer would give rise to unfavorable characteristics, including a lower current injection, larger turn-on voltage, and lower EL efficiency 22 , 31 , 34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of electron-hole recombination occurring in the GaN region is insignificant. However, the used MgO interlayer would give rise to unfavorable characteristics, including a lower current injection, larger turn-on voltage, and lower EL efficiency 22 , 31 , 34 .…”
Section: Resultsmentioning
confidence: 99%
“…One-dimensional (1D) wire semiconductors, such as micro/nanowires, nanoribbons, nanotubes and so on, have been extensively researched for constructing light-emitting diodes (LEDs) and laser diodes (LDs) due to their passive waveguides and strong confinement of electrons, holes, and photons 17 22 . The lasing features acquired from previously published 1D wired laser devices are currently multiple modes due to their larger dimensions than that of the lasing wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Recently reported room temperature electrically driven plasmonic laser can be described as nitride–oxide hybrid devices. [ 18 ] There are also similar reports about the electrically pumped random lasers based on n‐ZnO/p‐MgZnO core–shell nanowire heterostructures [ 19 ] or the electrically pumped random lasers with p‐diamond as a hole source. [ 20 ]…”
Section: Introductionmentioning
confidence: 73%
“…After conducting several strategies, they successfully realized the lasing of plasmonic structures at room-temperature. In 2019, Yang et al designed and experimentally demonstrated an electrically driven UV plasmonic nanowire laser at room-temperature, realized in a p-GaN/MgO/ZnO/MgO/Ag structure, as shown in Figure 5E (Yang X. et al, 2019 ). The high optical gain coefficient, large exciton binding energy, large oscillator strength, and material stability of ZnO was selected to ensure the performance of the device under high current injection and beneficial for a faster radiative lifetime (Djurišić et al, 2010 ; Sidiropoulos et al, 2014 ; Chou et al, 2015 ) due to its facile coupling with surface plasmon polaritons (SPPs).…”
Section: Nanowire Lasersmentioning
confidence: 99%